(untitled) (Innovative professional education, 2025)
The use of modern internet resources helps teachers diversify the educational process and make it more interactive. Platforms such as Worldwall, Classtime, and Napkin, as well as methods like word searches, emojis, anagrams, and comics, contribute to activating students’ cognitive activity and improving their language skills. Digital technologies enable the implementation of an individualized approach to learning, the development of students’ digital competencies, and their motivation for active participation in the educational process. Modern tools help make lessons more engaging, effective, and adaptable to the needs of modern education.